Pembuatan Kompos Dari Limbah Pertanian Sebagai Solusi Pengadaan Pupuk Secara Mandiri Oleh Masyarakat Di Desa Way Tuba Dan Campur Asri Kabupaten Way Kanan - Buhani, Buhani; Suharso, Suharso; Noviadi, Riko (Jurnal Pengabdi, 2018)
Waste management based on community participation that aims to implement the 4Rp concept (Reduce, Reuse, Recycle, Replace, Participation) has been implemented through the Regional Partnership Program (PKW) of Ministry of Research, Technology and Higher Education, by the PKW Team from the University of Lampung, in collaboration with Polinela and Government of Way Kanan District through the Environmental Services. This program was performed to manage the agricultural waste independently by the communities to reduce the amount of midden that must be managed at the landfill and it can provide an economic added value. These activities have been carried out in two villages, namely Way Tuba Village – Sub-district of Gunung Labuhan and Campur Asri Village, Sub-district of Baradatu, which have potency of the agricultural waste in Way Kanan District. In general, the results of these activities have increased community participation and knowledge of the paradigm of waste and waste management with the concept of the 4 Rp, procurement of fertilizers/compost independently, as well as being a pioneer of waste management based on active participation from the community. In addition, this program has provided solutions to the community to produce fertilizers/compost independently, either to be used for their own needs or sold to meet fertilizer/compost needs in the surrounding environment.